Immunoediting and angiogenesis in ovarian cancer - Duncan, Timothy Jake (2010)
Advances in the treatment of ovarian cancer have had a limited impact on prognosis over recent decades. Alternatives to the traditional surgical and chemotherapeutic approach are being sought. Many novel therapies relate to a greater understanding of the molecular changes which occur during carcinogenesis and the development of targeted therapies to exploit these abnormalities. The aim of this thesis was to investigate the prognostic significance of markers relating to tumour immunology, angiogenesis and apoptosis, through the use of Tissue Microarray Technology.